2019
DOI: 10.1002/ptr.6582
|View full text |Cite
|
Sign up to set email alerts
|

Scutellarin, a modulator of mTOR, attenuates hepatic insulin resistance by regulating hepatocyte lipid metabolism via SREBP‐1c suppression

Abstract: High levels of consumption of saturated lipids have been largely associated with the increasing prevalence of metabolic diseases. In particular, saturated fatty acids such as palmitic acid (PA) have been implicated in the development of insulin resistance (IR).Scutellarin (Scu) is one of the effective traditional Chinese medicines considered beneficial for liver diseases and diabetes. In this study, we investigated the effect of Scu on IR and lipid metabolism disorders in vitro and in high fat diet (HFD)-fed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Insulin resistance and metabolic dysfunction can promote the release of FAAs, and β‐oxidation of FFAs induces the generation of ROS and the release of pro‐inflammatory cytokines, thus promoting the progression of MAFLD 4 . During these processes, sterol regulatory element binding protein (SREBPs), important nuclear transcription factors involved in cholesterol and FA synthesis, play an important role in lipid metabolism 10 . Additionally, peroxisome proliferator‐activated receptors (PPARs), which are a group of nuclear regulatory factors involved in glucose and fat metabolism and the regulation of inflammatory cell activation and fibrotic processes, also participate in the pathogenesis of MAFLD 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin resistance and metabolic dysfunction can promote the release of FAAs, and β‐oxidation of FFAs induces the generation of ROS and the release of pro‐inflammatory cytokines, thus promoting the progression of MAFLD 4 . During these processes, sterol regulatory element binding protein (SREBPs), important nuclear transcription factors involved in cholesterol and FA synthesis, play an important role in lipid metabolism 10 . Additionally, peroxisome proliferator‐activated receptors (PPARs), which are a group of nuclear regulatory factors involved in glucose and fat metabolism and the regulation of inflammatory cell activation and fibrotic processes, also participate in the pathogenesis of MAFLD 11 …”
Section: Introductionmentioning
confidence: 99%
“…4 During these processes, sterol regulatory element binding protein (SREBPs), important nuclear transcription factors involved in cholesterol and FA synthesis, play an important role in lipid metabolism. 10 Additionally, peroxisome proliferator-activated receptors (PPARs), which are a group of nuclear regulatory factors involved in glucose and fat metabolism and the regulation of inflammatory cell activation and fibrotic processes, also participate in the pathogenesis of MAFLD. 11 Evidence has shown that intrauterine insults, such as poor nutrition, stress, and toxin exposure, during pregnancy may make offspring prone to chronic metabolic diseases such as cardiovascular diseases, hypertension, diabetes, and obesity in their adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…The role of autophagy in maintaining the homeostasis of hepatocyte lipids has been continuously confirmed, and diseases with lipid metabolism disorders, such as NAFLD, are often accompanied by different degrees of autophagy impairment (Allaire et al, 2019). In our previous study, we found that Scu improved lipid metabolism profiles in the serum and liver of C57BL/6 mice fed a HFD (Luan et al, 2020). Normal autophagy helps to maintain liver lipid homeostasis; therefore, the effect of Scu on liver lipid metabolism may be related to the improvement of autophagy function.…”
Section: Resultsmentioning
confidence: 90%
“…The mice in the test drug group were orally administered Scu (50 and 150 mg/kg) and Met (200 mg/kg) dissolved in a 0.2% CMC‐Na, respectively. Oral administration continued once a day for 18 days (Luan et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation